TaS2 nanosheet-based room-temperature dosage meter for nitric oxide - Qiyuan He; Qinglang Ma; Bo Chen; Zongyou Yin; Zhiyuan Zeng; Shixin Wu; Xiehong Cao; Xingyi Kong; Hua Zhang (APL Materials, 2014)
A miniature dosage meter for toxic gas is developed based on TaS2 nanosheets, which is capable of indicating the toxic dosage of trace level NO at room temperature. The TaS2 film-based chemiresistor shows an irreversible current response against the exposure of NO. The unique non-recovery characteristic makes the TaS2 film-based device an ideal indicator of total dosage of chronicle exposure.